Pengaruh Yoga Terhadap Dysmenorhea Pada Mahasiswi DIII Kebidanan Stikes Kuningan - Mala Tri Marliana; Suryani Soepardan; Bahiyatun . (Lembaga Penelitian Sekolah Tinggi Ilmu Kesehatan Kuningan, 2015)
Background: Dysmenorhea is cramping pain in the abdominal area began about 24 hours before the onset of menstrual bleeding and can last for 24-36 hours. 75% of girls have some of the problems associated with menstruation. One the causes of dysmenorhea is psychological factors, it’s Commonly happen in young women who are experiencing stress, usually when studying and being in a new environment, especially at the level I student. There are several ways to overcome dysmenorhea, one of them is yoga that teaches a set of techniques such as breathing, meditation and postures to improve strength and balance. Methods: The study was conducted by using quasi-experimental design with pretest and posttest. The number of respondents is 60 people, consisting of 30 control group and 30 treatment groups using total sample technique. The treatment group were trained and observed to do yoga as much as eight times during the month. Univariate analysis of the data is a frequency distribution table, bivariate analysis using paired t-test and Mann-Whitney test.Results: The average pain level dysmenorhea in the treatment group before being given yoga is 5 in pain scale and an average after being given yoga is 3 in pain scale. The average decrease in pain level dysmenorhea in 30 respondents having supplied yoga at 40.90. From the results of t test with significance level of 5% was obtained p value 0.000 <0.005, which means there is significant influence between yoga with a decrease dysmenorhe pain level. Conclusion: Yoga affected to the level of pain dysmenorhea. Suggestions: Young women need to do yoga because yoga is not only the muscles are trained, but no movement if the breath is very useful for relaxation in adolescents while experiencing dysmenorhea.